Various Incarnations of Lord Visnu as depicted in Indian Tradition & Culture - Panda, Prajna (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
India is a country of different traditional spiritual beliefs and religious faiths. People of India generally bind with the spiritual beliefs and sacred thoughts, since time immemorial. Hence, in India, generally we have the concept of various avatÁras (incarnations) of Lord Visnu or Shiva. The traditional scholars of India believe that the avataras are more in number and they are duly worshipped by the devotees of Lord Visnu or Lord Shiva in different ages of our Indian tradition and culture. This is really very interesting to know all about the sacred as well as mysterious incarnations of Lord Vishnu as rightly described in the Vedic texts and other spiritual texts, like epics and Puranas. But this paper will deal with the different incarnations of Lord Vishnu as described in Indian culture and tradition.